Penggunaan Teknologi dan Pembelajaran Digital di MA Pembangunan Syarif Hidayatullah Jakarta - Neli Kamalia Hana; Tifanka Risma Rosyidah; Heni Amanda; Amilatun Nasibah; Ridho Riyadli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The use of technology is not unfamiliar when applied in schools. The existence of this technology shifts conventional learning media into digital learning. The purpose of this research is to find out the technology used by MA development as a digital tool. This research is expected to provide information that in this digital era educational institutions also participate in utilizing technology as an alternative to learning, one example is MA Pembanngunan Syarif Hidayatullah Jakarta. The research method used is direct observation and interviews at MA Pembangunan Jakarta. The results and discussion are that MA Pembangunan Jakrta has implemented technology as a learning medium, by replacing notebooks and blackboards with tab and laptop technology. As well as using e-book learning modules. Using certain applications such as Canva to design modules and student assignments. The conclusion of this research is that MA Pembanguan Jakarta has successfully used technology in education and digital learning well, as evidenced by various achievements, for example in creative design competitions.